Bevacizumab plus erlotinib versus erlotinib alone for advanced EGFR-mutant non-small cell lung cancer: a meta-analysis of randomized clinical trials - Ruijian Li; Weiyi Li; Fang Zhang; Shanshan Li (European Journal of Medical Research, 2023)
Abstract Objective Previous studies showed that the combination of bevacizumab and erlotinib (combination therapy) significantly prolonged progression-free survival (PFS) but no overall survival (OS) compared to erlotinib alone (monotherapy) for advanced EGFR-mutant non-small cell lung cancer (NSCLC). Two phase III randomized controlled trials (RCTs) had reported the OS results in 2021. This meta-analysis aimed to include the results of the two RCTs to make a decision. Materials and methods We systematically searched relevant databases for RCTs on the use of bevacizumab plus erlotinib in advanced EGFR-mutant NSCLC. The main outcomes of interest were PFS, OS, and the reported hazard ratio (HR). Fixed-effect model was used to estimate pooled HR. Results Total 5 RCTs with 935 patients were eligible for this meta-analysis. All studies reached their primary study endpoints including PFS and OS. Compared to monotherapy, combination therapy remarkably prolonged PFS (HR = 0.60, 95% confidence interval CI 0.51–0.70; p < 0.00001); however, OS was similar between the two groups (HR = 0.90, 95% CI 0.76–1.08; p = 0.26). Subgroup analysis demonstrated that in deletion within exon 19 (19del) mutation subgroup, the combination therapy could only prolong PFS (HR = 0.60, 95% CI 0.47–0.76; p < 0.0001) but not OS (HR = 1.00, 95% CI 0.73–1.37; p = 1.00), and also in leucine-to-arginine substitution in exon 21 (L858R) mutation subgroup (HR = 0.59, p < 0.0001 and HR = 0.80, p = 0.18, respectively). For patients with brain metastasis at baseline, the combination therapy achieved a significant better PFS than the monotherapy (HR = 0.60, 95% CI 0.39–0.90; p = 0.01), and a better OS with the difference marginally significant (HR = 0.69, 95% CI 0.46–1.02; p = 0.06). Conclusions Combination of bevacizumab and erlotinib can prolong progression-free survival but not overall survival compared to erlotinib alone in advanced EGFR-mutant non-small cell lung cancer patients. The combination therapy not only can prolong progression-free survival but also has a tendency to prolong overall survival for patients with brain metastasis at baseline.